CSF VILIP-1 predicts rates of cognitive decline in early Alzheimer disease - Tarawneh, R. (Lippincott Williams & Wilkins, 2012)
OBJECTIVE: Measures of neuronal damage/dysfunction are likely good surrogates for disease progression in Alzheimer disease (AD). CSF markers of neuronal injury may offer utility in predicting disease progression and guiding prognostic and outcome assessments in therapeutic trials. Visinin-like protein-1 (VILIP-1) has demonstrated potential utility as a marker of neuronal injury. We here investigate the utility of VILIP-1 and VILIP-1/Aβ42 in predicting rates of cognitive decline in early AD. METHODS: Individuals with a clinical diagnosis of very mild or mild AD (n = 60) and baseline CSF measures of VILIP-1, tau, p-tau181, and Aβ42 were followed longitudinally for an average of 2.6 years. Annual assessments included the Clinical Dementia Rating (CDR), CDR–sum of boxes (CDR-SB), and global composite scores. Mixed linear models assessed the ability of CSF biomarker measures to predict rates of cognitive decline over time. RESULTS: Baseline CSF VILIP-1 and VILIP-1/Aβ42 levels predicted rates of future decline in CDR-SB and global composite scores over the follow-up period. Individuals with CSF VILIP-1 ≥560 pg/mL (corresponding to the upper tercile) progressed much more rapidly in CDR-SB (1.61 boxes/year; p = 0.0077) and global scores (−0.53 points/year; p = 0.0002) than individuals with lower values (0.85 boxes/year and −0.15 points/year, respectively) over the follow-up period. CSF tau, p-tau181, tau/Aβ42, and p-tau181/Aβ42 also predicted more rapid cognitive decline in CDR-SB and global scores over time. CONCLUSION: These findings suggest that CSF VILIP-1 and VILIP-1/Aβ42 predict rates of global cognitive decline similarly to tau and tau/Aβ42, and may be useful CSF surrogates for neurodegeneration in early AD.